MCSA Microsoft Windows 8.1 complete study guide - Shapiro, Jeffrey R.; Gibson, Darril (Sybex, 2015)
Over 90% of all personal computing devices run on Windows, and those certified on the newest version will be in high demand. This comprehensive resource prepares candidates to master all the exam objectives for the Microsoft Certified Solutions Associate (MCSA): Windows 8.1 exams 70-687 and 70-688, as well as the Upgrade exam 70-689. Study tools include a pre-assessment test, hands-on exercises, hundreds of review questions, exclusive practice exam questions, electronic flashcards, and over an hour of author-led videos. --